2020
DOI: 10.1002/jcp.30001
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rb1 attenuates microglia activation to improve spinal cord injury via microRNA‐130b‐5p/TLR4/NF‐κB axis

Abstract: Ginsenoside Rb1 (GRb1), a major ingredient of ginseng, has been found to be a potential protective agent in spinal cord injury (SCI) and in activated microgliainduced neuronal injury. This study discovered that GRb1 could facilitate miR-130b-5p expression in SCI rats and Toll-like receptor 4 (TLR4; a crucial player in inflammation) was a potential target of miR-130b-5p. Hence, we further investigated whether GRb1 could relieve SCI by reducing microglia-mediated inflammatory responses and neuronal injury via mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Recent studies have shown that miR‐130b‐5p has different functions in diverse types of tumours 23,24 . In addition, miR‐130b‐5p was reported to ameliorate activated microglia‐induced neuronal injury via the TLR4/NF‐κB signalling pathway 25 . A report has demonstrated that microRNA‐130b‐5p as a regulator for inhibition and treatment of NAFLD 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that miR‐130b‐5p has different functions in diverse types of tumours 23,24 . In addition, miR‐130b‐5p was reported to ameliorate activated microglia‐induced neuronal injury via the TLR4/NF‐κB signalling pathway 25 . A report has demonstrated that microRNA‐130b‐5p as a regulator for inhibition and treatment of NAFLD 15 .…”
Section: Discussionmentioning
confidence: 99%
“…23,24 In addition, miR-130b-5p was reported to ameliorate activated microglia-induced neuronal injury via the TLR4/NF-κB signalling pathway. 25 A report has demonstrated that microRNA-130b-5p as a regulator for inhibition and treatment of NAFLD. 15 However, the underlying mechanism of miR-130b-5p in HSC activation is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…GRb1 exerts significant antidepressant effects in chronic mild stress (CMS)-exposed rodents [ 21 ]. Already known that GRb1 regulates activation of microglia, protecting neurons from inflammatory, oxidative injury and promoting neurogenesis [ 22 , 23 ]. Few studies have focused on the relationship between antidepressant effects of GRb1 and microglia-mediated neuroinflammatory processes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, NF-κB pathway activation plays a positive role in the SCI development [ 2 , 10 ]. For example, GRB1 relieved SCI via altering miR-130b-5p/TLR4/NF-κB pathway [ 23 ]. circ_0000962 inhibited the inflammation in the SCI cell model via activating PI3K/Akt and inactivating NF-κB by sponging miR-302b-3p [ 7 ].…”
Section: Discussionmentioning
confidence: 99%